Rotifers from China (Western Guangdong Province), with description of Lecane zhanjiangensis sp. nov. (Rotifera: Monogononta: Lecanidae) - Wei, Nan; Jersabek, Christian D.; Yang, Yufeng (Zootaxa, 2019)
Littoral rotifers were collected in three prefectural cities of the little studied Western Guangdong Province (Yangjiang, Maoming and Zhanjiang) in April 2017 and in July 2018. Fifty-six monogonont taxa, including two subspecies/variations, were found. Lecane zhanjiangensis sp. nov., a new brackish-water species from the littoral zone of Shimenhe River Estuary in Zhanjiang, is described. It is characterized by large semicircular projections antero-laterally on the dorsal plate, each equipped with three to five minute spines, and a pair of large acutely pointed projections antero-laterally on the ventral head aperture margin. In addition, three new rotifer records for China, viz. Brachionus cf. caudatus var. indica Novotná-Dvořáková, 1963, Ptygura libera Myers, 1934 and P. thalenoiensis Meksuwan, Pholpunthin & Segers, 2011 are also presented. [Species zoobank registraion: http://zoobank.org/urn:lsid:zoobank.org:act:E91C0C2A-8656-4999-B71C-00F39456F7A0]